On Generalized q-deformed Fermionic Oscillators - Kim Thanh, Luu Thi (Communications in Physics, 2008)
In this work we consider a version of generalized q-deformed fermionic oscillators and some their applications. The corresponding coherent states are constructed. The statistical distribution of generalized q-deformed fermionic oscillators system, expressions for quadrature variances and the average particle number in the coherent states are calculated.